Occult gunshot injury of the temporal bone. Issue 3 (May 1997) - Geary, U M; Ritchie, D A; Luke, L C
Abstract : Increasing firearms violence has produced much public disquiet in recent months and Liverpool has seen a particularly well publicized spate of shootings. This is a case report of an initially occult intracranial injury which illustrates the unpredictable nature of missile trauma and the importance of computerised tomography in all cases of gunshot injury to the head.